2016
DOI: 10.1007/s40279-016-0510-4
|View full text |Cite
|
Sign up to set email alerts
|

Movement Patterns of the Knee During Gait Following ACL Reconstruction: A Systematic Review and Meta-Analysis

Abstract: Joint kinematics are restored, on average, 6 years following reconstruction, while knee external flexion moments remain lower than controls. Knee adduction moments are lower during early phases following reconstruction, but are higher than controls, on average, 5 years post-surgery. Findings indicate that knee function is not fully restored following reconstruction, and long-term maintenance programs may be needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 89 publications
9
99
0
Order By: Relevance
“…The ACLR and contralateral limbs changed similarly over the follow-up period, suggesting a bilateral adaptation to injury of a single limb. While it is well-documented that there are alterations in gait mechanics following ACLR, there exists some conflicting evidence on the direction and magnitude of such changes 6; 7 . These discrepancies may partially be due to the time at which the studies were conducted after reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ACLR and contralateral limbs changed similarly over the follow-up period, suggesting a bilateral adaptation to injury of a single limb. While it is well-documented that there are alterations in gait mechanics following ACLR, there exists some conflicting evidence on the direction and magnitude of such changes 6; 7 . These discrepancies may partially be due to the time at which the studies were conducted after reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…This change could be considered an improvement, as no difference was observed at 8-year follow-up in peak KFM as compared to the healthy control population, while a reduction in peak KFM was observed in both the ACLR and contralateral limbs at baseline versus control. Previous work has shown that ACLR subjects display reduced peak KFM 6 , an indication of diminished quadriceps function 48 , possibly due to reduced quadriceps strength, impaired neuromuscular control, compensatory movements, or lingering symptoms. Thus, the increase in KFM over time may indicate long-term continued recovery of quadriceps function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following ACLR, patients walk with smaller knee flexion–extension excursion and peak flexion, while also demonstrating lower knee flexion moments, in the involved compared with contralateral knee . These altered mechanics likely influence the direction and magnitude of the forces exerted on the patellofemoral cartilage during walking.…”
mentioning
confidence: 99%